Age and domain specific usability analysis of opinion visualisation techniques. Issue 8 (2nd August 2016) - Shamim, Azra; Balakrishnan, Vimala; Tahir, Muhammad; Ahsan Qureshi, Muhammad
ABSTRACT: This study analysed the impact of age and domain knowledge on the usability of some of the state-of-the-art opinion visualisation techniques. A questionnaire survey was designed to ask the users' level of agreement or disagreement about the selected opinion visualisation techniques against a set of information visualisation metrics. The data were collected by conducting seminars and using a web-based online questionnaire. We categorised participants ( N = 146) into three age groups (≤20 years: teenager; 21–30 years: young adults; >30: adults). According to domain knowledge, participants are classified into two groups, one having knowledge of human computer interaction (HCI users) and the other without this knowledge (non-HCI users). The collected data were analysed using an independent sample t -test and analysis of variance. It is concluded that there are significant differences between the perception of HCI and non-HCI users on visual appeal, understandability, user friendliness, intuitiveness, informativeness, usefulness, comprehensiveness, comparison ability, and pre-knowledge requirement. Moreover, age was found to be significant for visual appeal, comprehensiveness, intuitiveness, and pre-knowledge requirement.